Efficacy of bowel preparation regimens for colon capsule endoscopy: a systematic review and meta-analysis - Bjoersum-Meyer, Thomas; Skonieczna-Zydecka, Karolina; Cortegoso Valdivia, Pablo; Stenfors, Irene; Lyutakov, Ivan; Rondonotti, Emanuele; Pennazio, Marco; Marlicz, Wojciech; Baatrup, Gunnar; Koulaouzidis, Anastasios; Toth, Ervin (Endoscopy International Open, 2021)
Background and study aims Colon capsule endoscopy (CCE) is an alternative to conventional colonoscopy (CC) in specific clinical settings. High completion rates (CRs) and adequate cleanliness rates (ACRs) are fundamental quality parameters if CCE is to be widely implemented as a CC equivalent diagnostic modality. We conducted a systematic review and meta-analysis to investigate the efficacy of different bowel preparations regimens on CR and ACR in CCE.Patients and methods We performed a systematic literature search in PubMed, Embase, CINAHL, Web of Science, and the Cochrane Library. Data were independently extracted per the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The primary outcome measures (CR, ACR) were retrieved from the individual studies and pooled event rates were calculated.Results Thirty-four observational (OBS) studies (n = 3,789) and 12 randomized clinical trials (RCTs) (n = 1,214) comprising a total 5,003 patients were included. The overall CR was 0.798 (95 % CI, 0.764–0.828); the highest CRs were observed with sodium phosphate (NaP) + gastrografin booster (n = 2, CR = 0.931, 95 % CI, 0.820–0.976). The overall ACR was 0.768 (95 % CI, 0.735–0.797); the highest ACRs were observed with polyethylene glycol (PEG) + magnesium citrate (n = 4, ER = 0.953, 95 % CI, 0.896–0.979).Conclusions In the largest meta-analysis on CCE bowel preparation regimens, we found that both CRs and ACRs are suboptimal compared to the minimum recommended standards for CC. PEG laxative and NaP booster were the most commonly used but were not associated with higher CRs or ACRs. Well-designed studies on CCE should be performed to find the optimal preparation regimen.